Soil Science Education in the United States: History and Current Enrollment Trends - Brevik, Eric C.; Abit, Sergio; Brown, David; Dolliver, Holly; Hopkins, David; Lindbo, David; Manu, Andrew; Mbila, Monday; Parikh, Sanjai J.; Schulze, Darrell; Shaw, Joey; Weil, Ray; et al. (Journal of the Indian Society of Soil Science, 2015)
The study of soil science as an academic discipline was established more recently than the study of many other sciences, and in this brief 100 year time the teaching of soil science in the United States has undergone several significant changes. At its very beginning, soil science education took place in whichever institutions established programs of study. Over time, soils education in the United States became closely associated with agriculture and moved to the land grant institutions. Today, the land grant universities still form the backbone of soil science education in the United States, but soils concepts and topics are also taught in many other non-agricultural institutions around the country because of the varied practical uses of this resource. Soil science student enrollment was on the decline in the United States from the early 1990s through the early 2000s despite the fact that overall undergraduate student enrollment rose by about 11% over the same time period. A survey of United States institutions with soil science programs shows that student numbers have increased over the last seven years. While this increase in student numbers is positive news for the profession, there are long-term questions regarding where soil science fits in the academic structure of American institutions of higher education, as there appears to be an emerging shift in emphasis from an agricultural to an environmental focus.